0.4 then 1/2 then 60% is smallest to largest. Because if you make them all decimals then it would be 0.4 then 0.5 (1/2) then 0.6 (60%)
Answer:
x = 0, -4 and -3.
Step-by-step explanation:
The given expression is "3x to the power of 3 + 21x squared + 36x = 0".
We can write this expression as follows :
![3x^3+21x^2+36x=0](https://tex.z-dn.net/?f=3x%5E3%2B21x%5E2%2B36x%3D0)
Taking 3x common.
![3x(x^2+7x+12)=0\\\\3x=0\ \text{and}\ (x^2+7x+12)=0](https://tex.z-dn.net/?f=3x%28x%5E2%2B7x%2B12%29%3D0%5C%5C%5C%5C3x%3D0%5C%20%5Ctext%7Band%7D%5C%20%28x%5E2%2B7x%2B12%29%3D0)
x = 3
![x^2+7x+12=0\\\\x^2+3x+4x+12=0\\\\x(x+3)+4(x+3)=0\\\\(x+4)(x+3)=0\\\\x=-4,-3](https://tex.z-dn.net/?f=x%5E2%2B7x%2B12%3D0%5C%5C%5C%5Cx%5E2%2B3x%2B4x%2B12%3D0%5C%5C%5C%5Cx%28x%2B3%29%2B4%28x%2B3%29%3D0%5C%5C%5C%5C%28x%2B4%29%28x%2B3%29%3D0%5C%5C%5C%5Cx%3D-4%2C-3)
Hence, the solution of the given quadratic equation are x = 0, -4 and -3.
Answer:
Apprentice = $800
Journeyman = $1600
carpenter = $4000
Step-by-step explanation:
Let the apprentice earns X dollars.
Then ,
Journeyman will make 200% of apprentice's earning which is 2X.
Also,
Carpenter makes 250% of the earning that journeyman makes.
Which is 2.5(2X) = 5X
Their total earning should come to $6400.
Thus,
X + 2X + 5X = 6400
8X = 6400.
X = $800
So,
Earning of apprentice = X = $800
Earning of Journeyman = 2X = $1600
Earning of carpenter = 5X = $4000
Answer:
43.75 ft²
Step-by-step explanation:
= (l√(w/2)² + h²) + (w√(l/2)² + h²)
l & w become 3.5, and h becomes 6.
<em />
<em> </em>= (3.5√(3.5/2)² + 6²) + (3.5√(3.5/2)² + 6²)
<em>Step 1:Because this is a square pyramid, what you see above essentially becomes what you see below.</em>
<em />
= 2(3.5√(3.5/2)² + 6²)
<em>Step 2: Divide 3.5 by 2 to get 1.75.</em>
<em />
<em> </em>= 2(3.5√1.75² + 6²)
<em>Step 3: Square both 1.75 and 6 to get 3.0625 and 36 respectively.</em>
= 2(3.5√3.0625 + 36)
<em>Step 4: Add 3.0625 and 36 to get 39.0625.</em>
<em />
= 2(3.5√39.0625)
<em>Step 5: The square root of 39.0625 is 6.25.</em>
<em />
<em> </em>= 2(3.5 * 6.25)
<em>Step 6: Multiply 3.5 by 6.25 to get 21.875.</em>
<em />
= 2(21.875)
<em>Step 7: Multiply 2 by 21.875 to get 43.75.</em>
<em />
= 43.75 ft²
The lateral area of this pyramid is 43.75 ft².
<em />
<em />
We know that
case a)the equation of the vertical parabola write in vertex form is
y=a(x-h)²+k,
where (h, k) is the vertex.
Using our vertex, we have:
y=a(x-2)²-1
We know that the parabola goes through (5, 0),
so
we can use these coordinates to find the value of a:
0=a(5-2)²-1
0=a(3)²-1
0=9a-1
Add 1 to both sides:
0+1=9a-1+1
1=9a
Divide both sides by 9:
1/9 = 9a/9
1/9 = a
y=(1/9)(x-2)²-1
the answer isa=1/9case b)the equation of the horizontal parabola write in vertex form is
x=a(y-k)²+h,
where (h, k) is the vertex.
Using our vertex, we have:
x=a(y+1)²+2,
We know that the parabola goes through (5, 0),
so
we can use these coordinates to find the value of a:
5=a(0+1)²+2
5=a+2
a=5-2
a=3
x=3(y+1)²+2
the answer isa=3
see the attached figure